Dissolution, Solubility, and Stability of the Basic Ferric Sulfate-Arsenates [Fe(SO4)x(AsO4)y(OH)z·nH2O] at 25–45°C and pH 2–10 - Zongqiang Zhu; Hongqu Yang; Jie Liu; Yinian Zhu; Shen Tang; Lihao Zhang; Xingxing Wang (Journal of Chemistry)
Basic ferric sulfate-arsenates [FeSAsOH, Fe(SO4)x(AsO4)y(OH)z·nH2O] were prepared and characterized to study their potential fixation of arsenic in the oxidizing and acidic environment through a dissolution for 330d. The synthetic solids were well-shaped monoclinic prismatic crystals. For the dissolution of the sample FeSAsOH–1 [Fe(SO4)0.27(AsO4)0.73 (OH)0.27·0.26H2O] at 25–45°C and initial pH 2, all constituents preferred to be dissolved in the order of AsO43− > SO42− > Fe3+ in 1–3 h, in the order of SO42− > AsO43− > Fe3+ from 1–3 h to 12–24 h, and finally in the order of SO42− > Fe3+ > AsO43−. The released iron, sulfate, and arsenate existed dominantly as Fe3+/Fe(OH)2+/FeSO4+, HSO4−/SO42−/FeSO4+, and H3AsO40/H2AsO4−, respectively. The higher initial pHs (6 and 10) could obviously inhibit the release of Fe3+ from solid into solution, and the solid components were released in the order of SO42− > AsO43− > Fe3+. The crystal tops were first dissolved, and the crystal surfaces were gradually smoothed/rounded until all edges and corners disappeared. The dissociations were restricted by the Fe-O(H) breakdown in the FeO6 octahedra and obstructed by the OH− and AsO4 tetrahedra outliers; the lowest concentration of the dissolved arsenic was 0.045 mg/L. Based on the dissolution experiment at 25°C and pH 2, the solubility products (Ksp) for the basic ferric sulfate-arsenate [Fe(SO4)0.27(AsO4)0.73 (OH)0.27·0.26H2O], which are equal to the ion activity products (logˍIAP) at equilibrium, were calculated to be -23.04 ± 0.01 with the resulting Gibbs free energies of formation (ΔGfo) of −914.06 ± 0.03 kJ/mol.